(untitled) (Communications in Mathematical Research, 2021)
An H(2)-move is a local move of a knot which is performed by adding a half-twisted band. It is known an H(2)-move is an unknotting operation. We define the H(2)-unknotting number of a knot K to be the minimum number of H(2)-moves needed to transform K into a trivial knot. We give several methods to estimate the H(2)-unknotting number of a knot. Then we give tables of H(2)-unknotting numbers of knots with up to 9 crossings.